Pengaruh Gaya Kepemimpinan Transformasional Dan Kompensasi Terhadap Kinerja Pegawai KPRI Sejahtera Madiun - Amalia, Windy Rizki; Imron, Muhammad; Warnaningtyas, Hartirini (Universitas Merdeka Madiun, 2021)
Abstractâ€” This study aims to find out the partial and simultaneous influence of transformational leadership style variables and compensation on the performance of KPRI Sejahtera Madiun employees. The population in this study was kpri Sejahtera Madiun employees. Sampling using saturated sampling techniques. Samples taken by 40 employees. Research instruments use questionnaires. In this study, the data used were primary data, namely questionnaires measured using Likert scale and analyzed using multiple linear regression analysis with SPSS program version 25.0. The results of the tests have shown that: (1) Transformational leadership styles partially affect employee performance variables. (2) Compensation partially affects employee performance. (3) Transformational leadership style and compensation jointly (simultaneously) affect employee performance.Â Keywordsâ€”: Transformational Leadership Style; Compensation; Employee Performance.